Critical success factors (CSFs) framework for nanotechnology industry development in Malaysia - Faisal, Zulhumadi (2019)
Malaysia focuses on several industrial areas for rapid development, through selective cores for development in all Malaysia Plans. Nanotechnology received governmental support with its first inclusion in 2001 under the Eighth Malaysia Plan (20012005). However, its development of nanotechnology has its issues, such as slow development, lack of collaboration, etc. Many industry based reports highlighted the need for more comprehensive effort to facilitate development. This study aimed at developing a framework of critical success factors (CSFs) for effective nanotechnology development in the Malaysian nanotechnology industry. This research has identified problems from available resources related to current practice and knowledge in the nanotechnology industry, followed by identification of best practices, tools, and principles toward achieving better nanotechnology development. The Modified Delphi Technique was employed with two iterations, beginning with data collection interviews involving nanotechnology players in the industry, and ending with validation interviews with Malaysian nanotechnology bodies/agencies. In between the two interview rounds, thematic analysis of the data collection interviews was combined with factors identified in the literature review to develop a framework of CSFs that was verified in the validation interviews. Resource Based View (RBV) theory and Diffusion of Innovation (DOI) theory were identified as underpinning theories to explain the findings. The final framework highlighted four element factors, namely human resource and infrastructure (as explained by RBV), and consumer awareness and regulatory framework (as explained by DOI). This framework can be used as a term of reference for both Malaysian nanotechnology practitioners and academicians toward achieving greater nanotechnology development in Malaysia.